Estimating the Age of West Greenland Humpback Whales Through Aspartic Acid Racemization and Eye Lens Bomb Radiocarbon Methods - Boye, Tenna K.; Garde, Eva; Nielsen, Julius; Hedeholm, Rasmus; Olsen, Jesper; Simon, Malene (Frontiers in Marine Science, 2020)
To maintain a sustainable harvest of marine mammals, knowledge on key life history parameters such as age is essential. In West Greenland, humpback whale numbers were low during the 1980s due to past commercial whaling. However, the moratorium, which was enforced in 1986, had a positive effect on their abundance and by 2010 it was possible for Greenland to reopen the subsistence hunt on humpback whales in West Greenland. In this study, eyes were collected from 12 humpback whales taken in the subsistence hunt from 2010-2015 and used for age and growth estimation. Aspartic acid racemization (AAR) and bomb radiocarbon dating techniques were performed on the eye lens nuclei to obtain independent age estimates. Through AAR, 11 individuals were estimated to be younger than 20 years old and a single individual estimated to be 46 years old. Radiocarbon dating supported these estimates as all individuals had post-bomb pMC values. The Gompertz growth curve showed that humpback whales reach their asymptotic lengths around age ten and hence at a relatively young age. In conclusion, half a century after commercial whaling ended, the humpback whales feeding off West Greenland appear to consist mainly of young individuals. An age distribution that is likely attributed to a historical overexploitation and since a rapid increase in numbers following the moratorium.